Enhancing thermal-moisture comfort of a chest wader with lining for fishermen. Issue 17 (October 2017) - Liu, Zheng; Zou, Fengyuan; Zhan, Qing; Xu, Bugao
As basic protective clothing, a chest wader needs to be worn by fishermen during wading work. Its thermal and moisture performance would directly influence fishermen's comfort and health. In order to increase the thermal-moisture comfort for fishermen, this research aimed to design a new lining chest wader and to carry out both subjective and objective evaluations on its comfort properties. By simulating moisture absorption under a hydraulic pressure environment, we tested the water absorption and conductivity of the selected fabrics and water-absorbent resin materials, and used an appropriate combination of the fabric and the resin to cover different sweating areas of the human body. Ten subjects were recruited to conduct the wearing test on the chest wader to evaluate its thermal-moisture performance. The objective evaluation involved tracking the changes in temperature and relative humidity at four body parts when a participant wore the chest wader, while the subjective evaluation included a questionnaire about the wearing experience on the thermal-moisture comfort and operation convenience. The experimental results showed that the new lining enhanced the comfort significantly. Compared with the common chest wader, the new lining reduced the relative humidity of chest wader on average by 30% approximately, with the largest improvement being at the calf, followed by the thigh and crotch. The thermal-moisture performance of the chest wader was also influenced by the hydraulic pressure of the working environment and the ease allowance to the wearing body.